The use of cointegration and error correction modelling to investigate the influence of diabetes and associated medical services expenditure on economic growth in Malaysia - Tunku Salha, Tunku Ahmad; O'Neill, Ciaran, Prof.; Rowan, Neil J (Asian Economic and Social Society, 2013)
Link to publisher's homepage at http://www.aessweb.com/